Gharar dan Risiko dalam Transaksi Keuangan - Sirajul Arifin (Universitas Darussalam Gontor, 2010)
Business transactions are not always valid and often having wrong appearance. Gharar which tends to reflect uncertainty and construct injustice is categorized as invalid transaction. When the gain is uncertain and profit or lose are biased for one party side, the risk is appearing. Each transaction containing win-lose element, win in one side and lose in another side, is invalid and leads to haram consumption. In the financial transaction, the existence of gharar and risk is mainly caused by imperfect information (jahalah), of course there are other factors, in this regard, gambling element becomes a genuine characteristic in that transaction. This gambling element is very potential to create risk for all parties in the transaction. Indeed, risk is definitely unavoidable but it can be managed and controlled. As the result, risk management is an important way to control and reduce any possible risk.